Limitation of simple np-n tunnel junction based LEDs grown by metal-organic vapor phase epitaxy. (24th September 2020) - Robin, Y; Bournet, Q; Avit, G; Pristovsek, M; André, Y; Trassoudaine, A; Amano, H
Abstract: We show evidence that tunnel junctions (TJs) in GaN grown by metal-organic vapor phase epitaxy are dominated by defect level-assisted tunneling. This is in contrast with the common belief that highly doped layers (>10 20 cm −3 ) are required to narrow the TJ space charge region and promote the band-to-band tunneling. Our conclusion stems from the study and the review of the major doping limitations of carefully optimized p ++ and n ++ layers. The secondary ions mass spectroscopy profiles of GaN based TJ LEDs show a strong oxygen concentration located close to the p ++ /n ++ interface, typical for three dimensional growth. In addition, considering the doping limitation asymmetry and Mg carry-over, our simulations indicate a depletion region of more than 10 nm which is buried in a rough and defective n ++ layer. However, decent electrical characteristics of the studied TJ based LEDs are obtained, with a low penalty voltage of 1.1 V and a specific differential resistance of about 10 –2 Ω.cm 2 at 20 mA. This indicates that a common TJ could be greatly optimized by using a moderate doping (∼10 19 cm −3 ) while intentionally introducing local defects within the TJ.